Implementation of Problem-Based Learning Model with Animated Video Media to Improve Motivation, Creativity, and Economics Learning Outcomes at MA Salafiyah - Firly Farziyah Nurfy; Siti Umi Khayatun Mardiyah (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study investigates the implementation of the Problem-Based Learning (PBL) model integrated with animated video media to enhance student motivation, creativity, and learning outcomes in economics at MA Salafiyah. Employing a classroom action research approach with a pretest-posttest design, the research involved 35 grade XI students. Data were collected through observation sheets, motivation and creativity questionnaires, and learning outcome tests. The Shapiro-Wilk test was used to assess data normality, while the Wilcoxon Signed Rank Test evaluated the significance of differences between pretest and posttest scores. The findings reveal that the application of PBL with animated video media significantly improves student motivation, creativity, and learning outcomes. Students demonstrated increased engagement, generated more creative ideas, and showed deeper understanding of economic concepts. Motivation was reflected in higher posttest scores and active participation, while creativity was evident in the ability to propose innovative solutions and think critically. Learning outcomes improved substantially, with average scores rising from 46.142 (pretest) to 83.571 (posttest). The integration of animated video media in PBL created a dynamic and interactive learning environment that facilitated comprehension, stimulated interest, and encouraged practical application of knowledge. This study concludes that PBL supported by animated video media is an effective pedagogical strategy for improving educational quality in economics learning.